MANAJEMEN PENERAPAN PEMBELAJARAN BILINGUAL DI PONDOK PESANTREN MODERN MUHAMMADIYAH BOARDING SCHOOL JETIS PONOROGO JAWA TIMUR - Nurul Abidin; Syamsul Arifin; Nugraheni Fitroh Rezqi Syakarna (Universitas Muhammadiyah Ponorogo, 2022)
The era of the industrial revolution 4.0 encourages every field to be able to run with the times, not least in the field of education. Educational institutions must be able to improve the quality of services and learning so that they can produce graduates who are ready to fill every required field. One effort that can be done is to apply bilingualism in learning so that students have sufficient soft skills in English and Arabic.The purpose of this research was to determine the school management in implementing bilingualism in their learning both inside and outside the classroom, as well as the effectiveness of bilingual learning activities at Muhammadiyah Boarding School Jetis Ponorogo.This research uses a qualitative approach, with an ethnographic research design. This design in data collection uses direct observation techniques in the field, conducts in-depth interviews, and collects various documentary information. The data analysis technique is data reduction, data presentation, data validity validation and drawing conclusions.The results of this research are as follows: Bilingual learning at PP MBS Jetis Ponorogo is one of the visions and missions of MBS Jetis. MBS Jetis conceptualizes a bilingual learning strategy so that the achievement of language standards can be achieved. The implementation of bilingual learning at MBS Jetis is carried out in stages and on a scheduled basis, starting with activities after Fajr until Dhuhur, after which activities are continued in the dormitory. Bilingual learning that has been carried out at MBS Jetis has a positive impact both in terms of academic and non-academic.